2010
DOI: 10.2478/s11658-010-0031-3
|View full text |Cite
|
Sign up to set email alerts
|

TRPC expression in mesenchymal stem cells

Abstract: Transient receptor potential canonical (TRPC) channels are key players in calcium homeostasis and various regulatory processes in cell biology. Little is currently known about the TRPC subfamily members in mesenchymal stem cells (MSC), where they could play a role in cell proliferation. We report on the presence of TRPC1, 2, 4 and 6 mRNAs in MSC. Western blot and immunofluorescence staining indicate a membrane and intracellular distribution of TRPC1. Furthermore, the decrease in the level of TRPC1 protein caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
(44 reference statements)
0
11
0
1
Order By: Relevance
“…TRPV4-mediated Ca 2+ signaling is also a positive regulator of Sox9 and as such, has been shown to promote chondrogenesis 65 and in transducing the mechanical signals that support cartilage extracellular matrix maintenance and joint health 44 , 59 . TRPC1 is expressed during early chondrocyte expansion 66 , as well as being involved in the proliferation of mesenchymal stem cells 67 . We detected time, intensity, and PEMF dosage-dependent up-regulations of both TRPV4 and TRPC1 that closely correlated with the PEMF-induced expression pattern of chondrogenic markers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4-mediated Ca 2+ signaling is also a positive regulator of Sox9 and as such, has been shown to promote chondrogenesis 65 and in transducing the mechanical signals that support cartilage extracellular matrix maintenance and joint health 44 , 59 . TRPC1 is expressed during early chondrocyte expansion 66 , as well as being involved in the proliferation of mesenchymal stem cells 67 . We detected time, intensity, and PEMF dosage-dependent up-regulations of both TRPV4 and TRPC1 that closely correlated with the PEMF-induced expression pattern of chondrogenic markers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TRPV4 agonist-induced calcium entry can be directly associated with actomyosin network [23] . Transient Receptor Potential Channel 1 (TRPC1) and Transient Receptor Potential Channel 6 (TRPC6) expressed in MSCs [24] might also be cooperating with TRPV4 channels in mediating intracellular calcium signaling in response to mechanical stimuli [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Weick and co-workers demonstrated that TRPC1 and TRPC4 act as molecular targets for controlling neurite elongation in human embryonic stem cell-derived neurons (80). That MSCs express canonical TRPC1, 2, 4 and 6 mRNA and that TRPC1 may be involved in stem cell proliferation has been recently shown (81).…”
Section: Transient Receptor Potential (Trp) Pathwaysmentioning
confidence: 99%